Evaluation of Silvicultural Treatments in the Sustainability of Tropical Forests in the Northern Huetar Region, Costa Rica - Abarca-Valverde, Pablo (2020)
[Introduction]: The silvicultural treatments arise as one more tool of the forest management process, trying to maintain the productivity and profitability of the forest resource. [Objective]: Refining and release treatments were analyzed by evaluating ecological integrity, the productive potential of commercial wood and carbon dioxide as well as financial profitability according to biological, regulatory and financial harvest cycles. [Methodology]: This was achieved by performing the fifth measurement of the silvicultural experiment established in 1992 by the Forest Development Commission of San Carlos (CODEFORSA), the experiment consisted in establishing silvicultural treatments after the forest harvest in the management unit San Jorge in San Carlos, Costa Rica. [Results]: The treatments did not alter the reference values of ephemeral heliophyte species and basal area; the mean annual increase does not present significant differences between treatments, however the refinement test shows greater increases reflected in the net production of basal area and volume of commercial remnant mass, which were 27.42 % and 9.11 % higher, respectively. [Conclusions]: The financial and biological cutting cycle is completed four and five years earlier than the regulatory cutting cycle for the refining and releasing treatments, and is more profitable.